Implications of time-dependent molecular chemistry in metal-poor dwarf stars - Deshmukh, Siddhant Avinash; Ludwig, Hans-Günter (Astronomy and astrophysics, 2023)
Context: Binary molecules such as CO, OH, CH, CN, and C2 are often used as abundance indicators in stars. These species are usually assumed to be formed in chemical equilibrium. The time-dependent effects of hydrodynamics can affect the formation and dissociation of these species and may lead to deviations from chemical equilibrium. Aims: We aim to model departures from chemical equilibrium in dwarf stellar atmospheres by considering time-dependent chemical kinetics alongside hydrodynamics and radiation transfer. We examine the effects of a decreasing metallicity and an altered C/O ratio on the chemistry when compared to the equilibrium state. Methods: We used the radiation-(magneto)hydrodynamics code CO5BOLD and its own chemical solver to solve for the chemistry of 14 species and 76 reactions. The species were treated as passive tracers and were advected by the velocity field. The steady-state chemistry was also computed to isolate the effects of hydrodynamics. Results: In most of the photospheres in the models we present, the mean deviations are smaller than 0.2 dex, and they generally appear above log τ = −2. The deviations increase with height because the chemical timescales become longer with decreasing density and temperature. A reduced metallicity similarly results in longer chemical timescales and in a reduction in yield that is proportional to the drop in metallicity; a decrease by a factor 100 in metallicity loosely corresponds to an increase by factor 100 in chemical timescales. As both CH and OH are formed along reaction pathways to CO, the C/O ratio means that the more abundant element gives faster timescales to the constituent molecular species. Overall, the carbon enhancement phenomenon seen in very metal-poor stars is not a result of an improper treatment of molecular chemistry for stars up to a metallicity as low as [Fe/H] = −3.0.